Misleading Diagnosis of Dysgerminoma in a Young Asymptomatic Patient - Maharjan, O.; Bajracharya, N.; Dangal, G.; Karki, A.; Pradhan, H. K.; Shrestha, R.; Bhattachan, K.; Tiwari, K.; Bharati, S.; Maharjan, S. (Kathmandu University Medical Journal, 2020)
Dysgerminomas account for approximately one third of all malignant ovarian germ cell tumors (tumors arising from ovarian germinal elements) and are the most common ovarian malignancy detected during pregnancy. They are the only germ cell malignancy with a significant rate of bilateral ovarian involvement that is 15-20 percent. They have a variable gross appearance, but in general are solid, pink to tan to cream colored lobulated masses. They have the best prognosis of all malignant ovarian germ cell tumor variants. Two thirds are stage I at diagnosis, and prognosis is excellent even for those with advanced disease due to exquisite tumor chemosensitivity. The 5 year disease specific survival rate approximates 99 percent. This is a case report of a huge ovarian dysgerminoma in a young unmarried lady that was quite asymptomatic. She underwent laparotomy with right ovarian cystectomy.